The effects of delayed ischemic preconditioning on performance and recovery in repeated cycling bouts - Robitaille, C. A.; King, A. G.; Buchanan, C. A.; Dalleck, L. C. (International Journal of Research in Exercise Physiology, 2019)
Introduction: Ischemic preconditioning (IPC) is a technique of systematically occluding and reperfusingblood vessels that has shown to induce a biochemical cascade that increases the availability of nitric oxide (NO) and adenosine and enhances blood flow, endothelial function, and ATP regeneration. IPC has two physiological windows of protection; the first(immediate) window take place within the first 12 hours of treatment, while the second (delayed) takes place 24-72 hours post-treatment. The aim of this study was to evaluate its effects cyclists performing repeated incremental cycling bouts. Methods: In a randomized, crossover study, subjects received a 4 x 5min bilateral IPC treatment to the thigh. 24 and 48 hours after treatment, they performed an incremental cycling trial, followed by a 15-min recovery period, and then repeated the same cycling trial and recovery period. Time to fatigue (TTF) was recorded for each trial and heart rate (HR), blood lactate (La-), and blood Results: pressure (BP) were recorded throughout the recovery period. Despite individual variability, delayed IPC improved TTF (p<0.05), decreased performance decrement between trials, lowered HR and BP (p<0.05), which allowed cyclists to work at higher lactate levels (p<0.05). Conclusions: These results suggest that delayed IPC may be an effective performance and recovery strategy for endurance athletes.